Construction and countermeasure discussion on government performance evaluation model of air pollution control: A case study from Beijing-Tianjin-Hebei region. (1st May 2020) - Li, Yunyan; Huang, Shan; Yin, Chenxi; Sun, Guihua; Ge, Chang
Abstract: The main purpose of this paper is to build an objective and effective environmental performance evaluation model of air pollution control. Based on the severe air polluted region in China, that is Beijing-Tianjin-Hebei region, this evaluation model consists of four parts, including economic benefits, public service, government management and development potential, and uses the balanced scorecard theory. The weights of the indexes are measured by comprehensive evaluation method, which combined entropy weight method and analytic hierarchy process (AHP). To test the applicability of the evaluation method to different stages, back propagation (BP) neural network is introduced to simulate air pollution control in the future. The results reveal that the environmental performance of air pollution control in Beijing had an upward trend during 2010–2016, and the trend would continue in the next five years. The environmental performance of Tianjin continuously increased, especially from 2014 to 2016. Tianjin has great potential of air pollution control in the future. The environmental performance of air pollution control in Hebei fluctuated from 2010 to 2016 and it dropped to the lowest level in 2015, which mainly due to the large increase in number of days with air quality levelⅡor above compared with 2014 and the nonsignificant growth in the amount of expenditure on atmospheric prevention and control, the amount of investment in the control of industrial pollution sources and the number of law enforcement personnel. Moreover, the environmental performance of air pollution control closely related with industrial structure, especially with the proportion of the tertiary industry. The upgrading of urban industrial structure and the coordinated development of green industry should be implemented to restructure the environmental transformation in air-polluted region. Graphical abstract: Image 1000 Highlights: The traditional Balanced Scorecard is revised and applied into the environmental performance evaluation. The effective control of vehicle emission directly determines the air quality of Beijing. A fundamental improvement in air quality in Hebei requires a large amount of environmental investment. The environmental law enforcement is an important guarantee for air quality improvement of Tianjin.